Assessment of the groundwater quality in Sebha, Libya, for drinking purposes - Hamdan, Mohammed; Iessa, Kaes Rateb (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
The study examined water samples from wells in Sebha, analyzing their physicochemical properties such as pH, EC, TDS, Cl-, Na+, K+, Ca2+, Mg2+, NO3-, HCO3-, TH, and SO42-. The results revealed significant increases in EC, TDS, Cl-, Na+, K+, Ca2+, NO3-, TH, and SO42- concentrations. However, pH, Mg2+, and HCO3- remained within permissible limits set by Libyan and World Health Organization standards. The study also noted more pronounced changes in the physicochemical properties of water from wells in Abd-Alkafi1, Abd-Alkafi2, and Aljadeed on the western side of Sebha compared to those in Alnaserayah and Hajara on the eastern side. Correlation analysis showed strong positive correlations between EC-TDS, TH-Ca2+, and K+-Na+ at a significant level of p<0.01, and positive correlations at a significant level of p<0.05 between EC- Cl-, Cl–HCO3-, Cl– K+, Cl–Na+, SO42- - Na+, HCO3– NO3-, and HCO3– K+. The strong correlation between Na+ and Cl- indicated high concentrations of these ions in most samples, likely formed from chloride salts through chemical weathering. Similarly, a positive correlation between SO4– and Na+ suggested that some of these ions resulted from weathering of magnesium and sodium minerals. The Water Quality Index (WQI) categorized water from Alnaserayah and Hajara as suitable for drinking, while water from Abd-Alkafi2, Abd-Alkafi1, and Aljadeed was deemed poor quality. Comparing the current results to a 2001 study revealed a significant increase in the measured elements' concentrations and deterioration in water quality.